Sebaran Kadar Partikulat Debu Total dan Faktor Risiko Pekerja Dengan Kejadian ISPA di Industri Pembakaran Batu Kapur Kecamatan Margasari Kabupaten Tegal - Mirza Fathan Fuadi; Yura Witsqa Firmansyah; Muhammad Fadli R (Poltekkes Kemenkes Yogyakarta, 2022)
Air pollution is currently considered as the most serious environmental health risk in the world. One of the causes of an increase in pollutants in the air is the increase in the number of industries. Tegal Regency is one of the regencies in Central Java which has a limestone burning industry. Based on data from the environmental service of Tegal Regency, the total dust content around the industrial area exceeds the quality standard of 284 g/Nm3. This study aims to describe the distribution of total dust and analyze the relationship between total dust exposure and the incidence of ARI in limestone burning workers, Margasari District, Tegal Regency. This study used cross-sectional method. Total population of 160 respondents with a sample of 60 respondents, using random sampling. The results of statistical tests showed that the variables that had a relationship were exposure to inhaled dust (p = 0.031), working period (p = 0.046), total dust particulate levels (p = 0.048), use of PPE (p = 0.034). Based on the results of the study, the risk factors for the occurrence of ARI were 2 times greater in limestone burning workers who had exposure to inhaled dust above the NAV (?1 mg/m3). To prevent the occurrence of ARI, it is recommended that workers use complete PPE during the work process.